The resilience-enabling value of African folktales: The read-me-to-resilience intervention. (October 2017) - Theron, Linda; Cockcroft, Kate; Wood, Lesley
Resilience, or the process of adjusting well to adversity, draws on personal and social ecological resources (i.e., caregiving and community supports). Previous research—conducted mostly in the Global North—has shown that bibliotherapy offers a way to support children in identifying and utilizing resilience-enabling resources. In so doing, bibliotherapy has the potential to facilitate resilience. In this article, we confirm the resilience-supporting value of bibliotherapy for African orphans and vulnerable children (OVC). To do so, we report the quantitative and qualitative pre- and post-test results of the Read-me-to-Resilience Study ( N  = 345). This quasi-experimental study showed that African children who listened to indigenous resilience-themed stories had a significantly increased awareness of personal and community-based protective resources post-intervention, than those who did not. Interestingly, there was no significant increase in their perceptions of caregiving resources. The findings suggest that school psychologists and teachers should include resilience-enabling stories in their support of children who are orphaned. However, further research is needed on how best to use stories in ways that will enable children to identify caregiving resources.